Identification and level of ectoparasite intensity in goldfish (Carassius auratus) at fishery product inspection and certification center fish seed center - Ma'arif, Nur Ikhsan; Wirastuti, Aisyah Yoni; Saraya, Muhammad Agsa; Fauziyah, Nasywa Nur; Nofreeana, Andri (Politeknik Negeri Sambas, 2024)
Diseases and parasites that attack the fish body are often encountered in ornamental fish cultivation, so they can reduce the quality of the fish and cause fish death. Ectoparasites are parasites found outside the fish body. This study aimed to determine the type and intensity level of ectoparasite distribution in goldfish (Carassius auratus) cultivated at the Fishery Product Inspection and Certification Production Center (PPISHP) Fish Seed Center (BBI) Ciganjur, South Jakarta. A location survey and random sampling from three different rearing ponds were used. The goldfish samples obtained were 60 fish from three ponds in BBI Ciganjur. The results showed that the highest level of intensity of the Argulus sp. parasite was found in pond 2, the highest level of intensity of the Trichodina sp. parasite was found in pool 1, and the highest level of Lernea sp. parasite intensity was found in pools 1 and 3. The average infection level of each parasite showed that the intensity was relatively low.